Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.4142/jvs.2014.15.1.117
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic hyperthermal chemotherapy with indocyanine green: a novel cancer therapy for 16 cases of malignant soft tissue sarcoma

Abstract: Sixteen cases of malignant soft tissue sarcoma (STS; 10 canines and six felines) were treated with a novel triple therapy that combined photodynamic therapy, hyperthermia using indocyanine green with a broadband light source, and local chemotherapy after surgical tumor resection. This triple therapy was called photodynamic hyperthermal chemotherapy (PHCT). In all cases, the surgical margin was insufficient. In one feline case, PHCT was performed without surgical resection. PHCT was performed over an interval o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 31 publications
(34 reference statements)
1
4
0
Order By: Relevance
“…The present study revealed that combination therapy consisting of conservative surgery and PHCT in FVAS prevented recurrence of the tumor in the cases that had undergone no or one previous surgical resection. These results were comparable to those of a previous study ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The present study revealed that combination therapy consisting of conservative surgery and PHCT in FVAS prevented recurrence of the tumor in the cases that had undergone no or one previous surgical resection. These results were comparable to those of a previous study ( 15 ).…”
Section: Discussionsupporting
confidence: 91%
“…The PHCT procedure was performed as previously reported ( 15 ) under general anesthesia with isoflulene (DS Pharma Animal Health Co., Ltd., Osaka, Japan). In brief, ICG (25 mg/vial; Giagnogreen; Daiich Sankyo Co. Ltd, Tokyo, Japan) was dissolved in 9 ml saline (Otsuka Pharmacy, Co., Ltd., Tokyo, Japan) with an adjusted pH of 5.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In such contest, PDS and PDT may be of great advantage, allowing a thorough excision, thereby reducing the extent of the excision area and postoperative morbidity. PDT has already been studied in FISS, based on the use of indocyanine green combined to hyperthermal chemotherapy following conservative surgical resection [52]. In our series, cats were treated with acridine orange-based PDS and PDT, a treatment already tested in different pilot studies on malignant musculoskeletal tumors in humans [8, 41, 53–55].…”
Section: Discussionmentioning
confidence: 99%
“…Photodynamic hyperthermal therapy (PHT) (16,17), photodynamic hyperthermal CT (PHCT) (18,19) and CT were performed, with lupeol administered as an adjuvant therapy. PHT is a local treatment combining photo- ---187 187 Alive C06 II Partial ---180 180 Alive C07 II Partial PHCT --120 420 Alive C08 II Partial ---201 201 Alive C09 III Partial ---248 248 Alive C10 III Partial PHT --189 189 Alive C11 III Partial ---39 39 Alive DFT, disease-free time; ST, survival time; PHCT, photodynamic hyperthermal chemotherapy; PHT, photodynamic hyperthermal therapy.…”
Section: Subjectsmentioning
confidence: 99%